2007
DOI: 10.2139/ssrn.1690886
|View full text |Cite
|
Sign up to set email alerts
|

Do Fans Want Close Contests? A Test of the Uncertainty of Outcome Hypothesis in the National Basketball Association

Abstract: The National Basketball Association claims to sell entertainment. Part of that entertainment is close, competitive contests with uncertain outcomes. However, hometown fans want the home team to win. Hence, the optimal probability that the home team wins a game, from the perspective of maximizing demand, lays somewhere between 0.5 and 1.0. Using data from individual games for the 2001-02 season, this optimal probability was estimated to be approximately 0.66. Fans want their home team to have about twice the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 20 publications
7
27
0
Order By: Relevance
“…Surdam, (Surdam, 2009), finds this result may be dependent upon individual team fan base preferences. In the National Basketball Association, Rascher and Solmes (Rascher and Solmes, 2007) find similar results to those of MLB. Paul and Weinbach (Paul and Weinbach, 2007) find that uncertainty of outcome is associated with higher viewership for National Football League Monday night broadcast.…”
Section: Literaturesupporting
confidence: 57%
See 1 more Smart Citation
“…Surdam, (Surdam, 2009), finds this result may be dependent upon individual team fan base preferences. In the National Basketball Association, Rascher and Solmes (Rascher and Solmes, 2007) find similar results to those of MLB. Paul and Weinbach (Paul and Weinbach, 2007) find that uncertainty of outcome is associated with higher viewership for National Football League Monday night broadcast.…”
Section: Literaturesupporting
confidence: 57%
“…Competitive balance can refer to the season-long race between teams for a league championship, or the closeness and uncertainty of outcome of given a contest, game, or match (Rascher & and Solmes (2007)). Contests/games with a higher level of outcome uncertainty are more entertaining, leading to a larger consumer demand for game tickets and broadcasting rights.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some studies supporting the conventional uncertainty of outcome hypothesis have shown that competitive balance in sport is correlated with attendance demand (e.g. Meehan, Nelson and Richardson, 2007;Rascher and Solmes, 2007). If this is correct, then any decline in competition may result in reduced income from gate receipts.…”
Section: Theoretical Considerations and Practical Relevancementioning
confidence: 99%
“…Borland and Macdonald (2003) survey the major findings of numerous studies on the relationship between attendance and outcome uncertainty, revealing inconclusive evidence. In North American sports, Knowles et al (1992) examined the determinants of stadium attendance at Major League Baseball games, and Rascher and Solmes (2007) and Berri et al (2004) did the same for National Basketball Association (NBA) games, revealing a weakly positive correlation between match uncertainty and the size of attendances. In North American sports, Knowles et al (1992) examined the determinants of stadium attendance at Major League Baseball games, and Rascher and Solmes (2007) and Berri et al (2004) did the same for National Basketball Association (NBA) games, revealing a weakly positive correlation between match uncertainty and the size of attendances.…”
Section: Literature Reviewmentioning
confidence: 99%